2014
DOI: 10.1590/1413-81232014195.13932013
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da usabilidade do Guia Alimentar Digital móvel segundo a percepção dos usuários

Abstract: Avaliação da usabilidade do Guia Alimentar Digital móvel segundo a percepção dos usuáriosEvaluation of the usability of a mobile Digital Food Guide based on user perception

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
7

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 15 publications
1
10
0
7
Order By: Relevance
“…The use of digital technology for recording dietary data is an innovation that has been experimented successfully in other countries 7 , and its usability in Brazil has proven to be promissing 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The use of digital technology for recording dietary data is an innovation that has been experimented successfully in other countries 7 , and its usability in Brazil has proven to be promissing 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The app has an intuitive design, it is easy to use and provide objective information about its operation and functions 13 . Its functions allow entering information about all foods and drinks consumed, identifying the item and informing the amounts in common household measures or according to weight for each one of the meals (breakfast, mid-morning snack, lunch, mid-afternoon snack, dinner, and late-evening snack).…”
Section: E T H O D Smentioning
confidence: 99%
“…Over the past few years, several Internet and mobile telephony applications have been developed to promote self-care aiming at motivating users to adopt a healthy lifestyle. The advances and diffusion of this technology also contribute to the usability of mobile platforms for apps that promote good health and wellbeing 13 Another benefit of this technology is that mobile apps help professionals assess dietary intake 9,14 . It has been shown that the use of digital media to collect data on dietary intake is more effective and less time consuming for the interviewer since gathering and analyzing food intake data is a complex task 7,14,15 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mobile health (mHealth) integrates mobile technology with public health practices with the purpose of improving communication and achieving healthy lifestyles [22]. Studies have reported that mHealth interventions may increase access to health care services; initiate the process of behavior changes or increase motivation for small changes; and spread knowledge, especially if aimed at receptive consumers [23][24][25][26]. Adolescents and young adults form the audience that readily accepts and adopts new technologies; thus, the diffusion effect may be stronger among them [27].…”
Section: Introductionmentioning
confidence: 99%